HUBUNGAN PELAYANAN INFORMASI OBAT DENGAN TINGKAT KEPATUHAN PASIEN HIPERTENSI - Kemal, Amir (Politeknik Tiara Bunda, 2021)
Drug information services are very important in supporting the management and use of drugs rationally. Drug information services are very necessary, especially since many patients have not received adequate drug information. The purpose of this study was to see the relationship between drug information services and the level of compliance of hypertensive patients at the Sikumana Health Center in Kupang City. This study is a non-experimental study with a descriptive research design with a prospective approach. The sampling technique used was purposive sampling. Respondents in this study were all patients suffering from high blood pressure (Hypertension) at the Sikumana Health Center in Kupang City with a total of 50 people. Furthermore, the data was analyzed using Kendal's Tau-B correlation analysis with a significance level of p <0.005. Based on the results of statistical tests using Kendal's Tau-B correlation, a significant value of 0.004 was obtained, stating that there was a relationship between drug information services and the level of compliance of hypertensive patients, with a correlation coefficient value of 0.348 with a degree of relationship that is sufficient correlation, so it can be concluded that there is a relationship between drug information services and the level of compliance of hypertensive patients and the degree of relationship that is sufficient correlation.